Moral Hazard and the Composition of Transfers: Theory with an Application to Foreign Aid - Bazoumana Ouattara; J. Atsu Amegashie; Eric Strobl (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
The paper presents a theoretical and empirical analysis of a donor's choice of the composition of unrestricted and in-kind/restricted transfers to a recipient and how this composition is adjusted in response to changes in the moral hazard behavior of the recipient. In-kind or restricted transfers may be used, among others, to control a recipient's moral hazard behavior but may be associated with deadweight losses. Within the context of foreign aid, we use a canonical political agency model to construct a simple signaling game between a possibly corrupt politician in a recipient country and a donor to illustrate the donor's optimal choice of tied (restricted) and untied foreign aid. We clarify the condition under which a reduction in the recipient's moral hazard behavior (i.e., improvement in the level of governance) leads to a fall in the proportion of tied aid. We test the predictions of our theoretical analysis using data on the composition of foreign aid by multilateral and bilateral donors.
Keywords: D73; F35; H87; I38; 330; Moral Hazard; Foreign Aid; Panel Data